2010
DOI: 10.1029/2009ja014597
|View full text |Cite
|
Sign up to set email alerts
|

Role of magnetosheath force balance in regulating the dayside reconnection potential

Abstract: [1] When the interplanetary magnetic field (IMF) is southward, most of the ionospheric potential is generated by merging between the IMF and the magnetospheric field. Typically, the ionospheric potential responds linearly to the magnitude of the southward IMF. However, when the IMF magnitude is large, the ionospheric potential saturates and it becomes relatively insensitive to further increases in the IMF magnitude. We present evidence from simulations that under purely southward IMF conditions, the value of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
177
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(206 citation statements)
references
References 50 publications
29
177
0
Order By: Relevance
“…Much further work is required to develop a full understanding of magnetosheath physics and of how magnetosheath properties affect solar wind-magnetosphere interaction in many important ways [e.g., Lavraud and Borovsky, 2008;Lopez et al, 2010Lopez et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much further work is required to develop a full understanding of magnetosheath physics and of how magnetosheath properties affect solar wind-magnetosphere interaction in many important ways [e.g., Lavraud and Borovsky, 2008;Lopez et al, 2010Lopez et al, , 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Another important parameter in solar wind-magnetosphere interaction is the solar wind Alfvén Mach number M A : the ratio of the bulk solar wind to Alfvén speeds [Lavraud and Borovsky, 2008;Borovsky, 2008]. This is because M A directly controls the bow shock compression ratio and the value of the plasma b (ratio of the thermal plasma to magnetic pressures) in the downstream magnetosheath, which in turn changes which of the magnetic or thermal plasma forces dominates the dynamics in the magnetosheath [Lavraud and Borovsky, 2008;Borovsky et al, 2009;Lopez et al, 2010Lopez et al, , 2011. As a buffer region between the solar wind and magnetosphere, the magnetosheath plays a pivotal role in the global interaction.…”
Section: Introductionmentioning
confidence: 99%
“…This reduces the geoeffective lengtha scale length indicative of the amount of solar wind flow potential that is applied to the magnetosphere (Burke et al 1999). While Lopez et al (2010) used this dynamic to help explain CPCP saturation, found it applicable to the present case of non-saturated CPCP reductions when polar wind-like outflow is included in global simulations. Garcia et al (2010) presented supporting evidence in simulations that used the LFM with prescribed outflow relegated to the nightside ionosphere only.…”
Section: Heavy Ions In Self Consistent Global Modelsmentioning
confidence: 99%
“…noted that as outflow fuels the ring current, the magnetosphere expands, especially at the flanks, leading to the CPCP reduction. Lopez et al (2010) described the physical mechanisms behind this: as the magnetosphere becomes a blunter obstacle to the solar wind, the solar wind flow has to traverse a greater distance across a wider magnetosheath and hence experiences a greater deflection due to magnetosheath forces. This reduces the geoeffective lengtha scale length indicative of the amount of solar wind flow potential that is applied to the magnetosphere (Burke et al 1999).…”
Section: Heavy Ions In Self Consistent Global Modelsmentioning
confidence: 99%
“…[4] Several studies have examined the relationship between (1) enhanced CPCP and the southward interplanetary magnetic field (IMF), and (2) enhanced ring current response and the southward IMF [e.g., Gonzalez et al, 1994;Russell et al, 2001;Siscoe et al, 2002aSiscoe et al, , 2002bSiscoe et al, 2004;Merkin et al, 2005;Ridley, 2007;Kivelson and Ridley, 2008;Lavraud and Borovsky, 2008;Lopez et al, 2009;Lopez et al, 2010]. Gonzalez et al [1994] found that ring current response grows in response to prolonged periods of southward IMF in data.…”
Section: Introductionmentioning
confidence: 99%